The impact of the quality of democracy on the economic growth of provinces in Indonesia - Nairobi Nairobi; Nur Rita Santi; Fadeli Yusuf Afif (Goodwood Publishing, 2021)
Purpose: The impact of democracy on economic growth is an interesting study of economic institutions and there is still debate about the impact on economic growth. One side of the research finds that democracy has a significant and positive impact on economic growth, but the other side states that the improvement of the country's democracy causes economic growth to decline. This study aims to examine the impact of the quality of democracy on economic growth at the provincial level in Indonesia. Research methodology: The data used in this study use panel data using the Eviews 9.0 analysis tool, so that the best method named the Random Effect Model is obtained. Result: The results show that democracy in Indonesia has a significant impact on economic growth and there is a positive trend in the long run. Other variables used are labor and foreign investment, which statistically, if these variables occur, can increase economic growth in Indonesia and increase employment and data on foreign investment play a role in driving economic growth. Economic growth in Indonesia is already in good condition and the economic growth that occurs is convergence growth which shows that some provinces that are poor/underdeveloped can catch up with developed provinces. Limitations: This study uses fairly short time-series data, so that the addition of a longer time-series will of course give better results. Contribution: Improvements in democracy in Indonesia should also strengthen democratic norms that apply in society, such as reducing corrupt behaviors, especially political corruption and money politics to get public office because if this behavior cannot be corrected, then democracy will have little impact on the economy.